Dynamic Resolution in GPU-Accelerated Volume Rendering to Autostereoscopic Multiview Lenticular Displays. (19th June 2008) - Ruijters, Daniel
Abstract : The generation of multiview stereoscopic images of large volume rendered data demands an enormous amount of calculations. We propose a method for hardware accelerated volume rendering of medical data sets to multiview lenticular displays, offering interactive manipulation throughout. The method is based on buffering GPU-accelerated direct volume rendered visualizations of the individual views from their respective focal spot positions, and composing the output signal for the multiview lenticular screen in a second pass. This compositing phase is facilitated by the fact that the view assignment per subpixel is static, and therefore can be precomputed. We decoupled the resolution of the individual views from the resolution of the composited signal, and adjust the resolution on-the-fly, depending on the available processing resources, in order to maintain interactive refresh rates. The optimal resolution for the volume rendered views is determined by means of an analysis of the lattice of the output signal for the lenticular screen in the Fourier domain.